"y^2-2xyy'+x^2(y')^2-\\frac{4}{(y')^2}=0\\\\\na=1, b=-2xy', c=x^2(y')^2-\\frac{4}{(y')^2}\\\\\nD=b^2-4ac=4x^2(y')^2-4(x^2(y')^2-\\frac{4}{(y')^2})=\\\\\n=\\frac{16}{(y')^2}\\\\\n1) y=\\frac{2xy'-\\frac{4}{y'}}{2} \\implies y=xy'-\\frac{2}{y'} (*)"
this is the Clairaut's equation, make a substitution
"y'=p, dy=p dx"
then
"y=xp-\\frac{2}{p}\\\\\ndy=pdx +xdp+\\frac{2}{p^2}dp\\\\\npdx=pdx +xdp+\\frac{2}{p^2}dp\\\\\n(x+\\frac{2}{p^2})dp=0\\\\\na) dp=0 \\implies p=c \\implies y=xc-\\frac{2}{c}"
is the general solution
"b) x+\\frac{2}{p^2}=0"
let's say "x<0" then
"p=\\pm\\sqrt\\frac{2}{-x} \\implies y'=\\pm\\sqrt\\frac{2}{-x} \\implies\\\\\ny=\\pm(-2\\sqrt2 \\sqrt{(-x)}) +c_1"
substitute y in (*)
"\\pm(-2\\sqrt2 \\sqrt {( -x )})+c_1=\\\\\n=x(\\pm\\sqrt\\frac{2}{-x})-(\\pm\\frac{2}{\\sqrt\\frac{2}{-x}})\\implies\\\\\nc_1=0"
then "y=\\pm(-2\\sqrt2 \\sqrt{(-x)})" are solutions of the equation.
2) "y=\\frac{2xy'+\\frac{4}{y'}}{2} \\implies y=xy'+\\frac{2}{y'} (**)"
this is the Clairaut's equation, make a substitution
"y'=p, dy=p dx"
then
"y=xp+\\frac{2}{p}\\\\\ndy=pdx +xdp-\\frac{2}{p^2}dp\\\\\npdx=pdx +xdp-\\frac{2}{p^2}dp\\\\\n(x-\\frac{2}{p^2})dp=0\\\\\na) dp=0 \\implies p=c \\implies y=xc+\\frac{2}{c}"
is the general solution
"b) x-\\frac{2}{p^2}=0"
let's say "x>0" then
"p=\\pm\\sqrt\\frac{2}{x} \\implies y'=\\pm\\sqrt\\frac{2}{x} \\implies\\\\\ny=\\pm2\\sqrt2 \\sqrt x +c_2"
substitute y in (**)
"\\pm2\\sqrt2 \\sqrt x+c_2=\\pm x\\sqrt\\frac{2}{x}+\\frac{2}{\\pm\\sqrt\\frac{2}{x}}\\implies\\\\\nc_2=0"
then "y=\\pm2\\sqrt2 \\sqrt x" are solutions of the equation.
Comments
Leave a comment